The eye book a complete guide to eye disorders and health - Cassel, Gary H., 1953- (Johns Hopkins Press health book., 2021)
"This is the second edition of an encyclopedic reference work of consumer health about the adult human eye. It covers common eye complaints such as dry eye, ocular migraine, device-related eyestrain, and conjunctivitis, along with newer forms of laser eye therapy and lens implants. The second edition features a new chapter on cosmetics and the eye, along with updated content about diagnostic testing, new forms of eyeglass materials, colored contacts, and therapies for medical conditions for all areas of the eye"--